2007
DOI: 10.1037/0022-0663.99.3.492
|View full text |Cite
|
Sign up to set email alerts
|

Teaching high school students to use heuristics while reading historical texts.

Abstract: The purpose of this study was to test the effectiveness of different types of instruction and texts on high schools students' learning of (a) history content and (b) a set of heuristics that historians use to think critically about texts. Participants for the study were 128 male and 118 female students, ages 16 and 17 years, from 2 high schools in the western United States. Eight history classrooms were randomly assigned to 1 of 4 interventions: (a) traditional textbooks and content instruction, (b) traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 33 publications
10
143
1
10
Order By: Relevance
“…examples by Bohan & Davis, 1998;Nokes et al, 2007); (2) formulating a problem statement calling for knowledge transformation (van Drie et al, 2006); (3) Each of these steps was taught through a combination of direct instruction and individual or group work. For example, work on the second step 'formulating a problem statement' started with the instructor presenting a theoretical introduction on students' ability to ask historical questions, based on previous work by Logtenberg (2012).…”
Section: Workhopmentioning
confidence: 99%
“…examples by Bohan & Davis, 1998;Nokes et al, 2007); (2) formulating a problem statement calling for knowledge transformation (van Drie et al, 2006); (3) Each of these steps was taught through a combination of direct instruction and individual or group work. For example, work on the second step 'formulating a problem statement' started with the instructor presenting a theoretical introduction on students' ability to ask historical questions, based on previous work by Logtenberg (2012).…”
Section: Workhopmentioning
confidence: 99%
“…(p. 305) Such insights about disciplines slowly have begun to be translated into new models for addressing literacy instruction within the disciplines. Wineburg (1991), for example, found that historians engaged in contextualization, sourcing, and corroboration as they read historical documents, and researchers have studied attempts to teach students to use these strategies to comprehend and critically analyze history texts, albeit with mixed results (Hynd-Shanahan et al, 2004;Nokes, Dole, & Hacker, 2007). Similarly, in science, researchers have been developing approaches and strategies based on emerging descriptions of how scientists read (Hand, 1999;Hand & Prain, 2002;Holliday & Benson, 1991;Hynd, McWhorter, Phares, & Suttles, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…We integrated existing models of the cognitive activities involved in historical reasoning in order to account for the properties of strategy use (see Carretero et al 1997;Nokes et al 2007; van Drie and van Boxtel 2008). In doing so, we distinguish between superordinate and subordinate categories of constructs.…”
Section: The Role Of Goals In Learning Through Historical Inquirymentioning
confidence: 99%
“…In doing so, we synthesized theoretical constructs from models of SRL (Winne 2001(Winne , 2005Winne and Hadwin 1998, 2010 and historical reasoning (Carretero et al 1997;Nokes et al 2007; van Drie and van Boxtel 2008). There are several basic assumptions that underlie domain-specific accounts of SRL, which are also shared with domain-general models.…”
Section: Introductionmentioning
confidence: 99%